2015
DOI: 10.1039/c5ra18271a
|View full text |Cite
|
Sign up to set email alerts
|

A study on the trastuzumab conjugation at tyrosine using diazonium salts

Abstract: Herein, we report on the conjugation of trastuzumab with 2,5-difluorobenzene diazonium tetrafluoroborate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…Interestingly, another study using a different stable diazonium reagent reported complete selectivity towards tyrosine at physiological pH when modifying the antibody trastuzumab. 22 Since the development of the first stable diazonium reagent for tyrosine modification, the variety of functional groups that can be introduced with such compounds has been expanded, enabling bioorthogonal click chemistry such as azide–alkyne cycloaddition 23 or tetrazine-ene reactions. 24 In addition, the method has been applied to many proteins, including the conjugation of the small-molecule inhibitor aplaviroc to a series of anti-HIV antibodies.…”
Section: Chemical Approaches For Tyrosine Modificationmentioning
confidence: 99%
“…Interestingly, another study using a different stable diazonium reagent reported complete selectivity towards tyrosine at physiological pH when modifying the antibody trastuzumab. 22 Since the development of the first stable diazonium reagent for tyrosine modification, the variety of functional groups that can be introduced with such compounds has been expanded, enabling bioorthogonal click chemistry such as azide–alkyne cycloaddition 23 or tetrazine-ene reactions. 24 In addition, the method has been applied to many proteins, including the conjugation of the small-molecule inhibitor aplaviroc to a series of anti-HIV antibodies.…”
Section: Chemical Approaches For Tyrosine Modificationmentioning
confidence: 99%
“…Aryl diazonium ions have undergone a renaissance in the bioconjugation literature, , but their chromophoric properties enabled them to be one of the first reliable tools to modify proteins dating back to the early 20th century. ,, While useful, many aryl diazonium ions suffer from the requirement of generation immediately prior to the experiment due to their short half-lives in solution and general instability. Recognizing the promise of aryl diazonium ions as robust small-molecule covalent probes, triazabutadienes were developed as a new biochemical tool for their generation .…”
Section: Introductionmentioning
confidence: 99%
“…However, our experiment showed that 229 Cys and 232 Cys on the same heavy chain were connected by modification with a (benzofuranyl)­methine unit, presumably because 229 Cys and 232 Cys are close to each other. In addition, our experiment also showed a single S-arylation at some cysteine residues and azo coupling at some tyrosine residues , (Figure ). As the yield of the whole process in this preliminary experiment including photolabeling and protein digestion is low, no reliable quantitative analysis can be achieved.…”
Section: Resultsmentioning
confidence: 99%